CHALLENGES FACING ACCOUNTING IN LIGHT OF SUSTAINABLE DEVELOPMENT - Researcher / Bushra Hamed Al-Asami (Scholar Express Journals, 2024)
Accounting faces many challenges in light of sustainable development related to addressing the environmental, social and economic dimensions of business operations, and the aim of the research is to understand and identify the challenges facing accounting in light of sustainable development, as well as proposing and identifying solutions to those challenges and directing legislation and policies related to that, and the problem of research lies in the fact that traditional accounting focuses only on the financial element without focusing on the environmental and social influences of business activities, which exposes organizations to environmental and social risks, which leads to Hindering sustainable development. The research was divided into two axes, the first axis was devoted to knowing the current role of accounting in light of sustainable development and identifying weaknesses, either the second axis was quotas to assess the effects resulting in the inclusion of sustainable development, i.e. estimating the impact of including sustainable development concepts in accounting on financial performance and organizational behavior, and the results of the research indicated the need to develop accounting standards in order to be able to provide comprehensive information that keeps pace with sustainable development, which takes into account the environmental and social impacts, as well as enhancing training and education for accountants to increase their awareness. The importance of sustainable development and how to include it in their work
Keywords: increase; enhancing; education